If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(2x=1)=-14x-7
We move all terms to the left:
-7(2x-(1))=0
We multiply parentheses
-14x+7=0
We move all terms containing x to the left, all other terms to the right
-14x=-7
x=-7/-14
x=1/2
| 3y=7y-8/3 | | 7z=-20+8z | | -4(n+6)=12(n+10) | | 41=12y | | 5(-1+2a)=60 | | -9m+3=21 | | 12x-6-5=19 | | -119=-6(8p-3)+7 | | 11x-1+24=12+13 | | 2(w+3)=6+2w | | 8x2−x+2=2 | | 18+20c=5c-15+18c | | 28=8x+12=7x | | 1x+2x+(x+8)=180 | | m-29=58 | | -3(4x+3)=12x+9 | | 8x^2−x+2=2 | | 5/4=−4c+4/1 | | 9d-9=d-3 | | 2/5x+2/3=4/5 | | 7a+-3=7a-3 | | 2/5=w-2/2 | | -1/2x+3/14=-2/7 | | 2x+9√x-5=0 | | 7(6-12k)-3=-2k-5(11k+3) | | 10+.10x=35 | | 375÷500=t | | x-34=54 | | 4n+3=5/7 | | 4.2x-3=0.5(8.4x=6) | | 13.1w=4.44+14.3w | | x^2+-16x+16=0 |